Standarisasi Istita’ah Kesehatan Terhadap Kenyamanan Jama’ah Untuk Pelaksanaan Ibadah Pada Haji 2024 - Muhammad Hakam Arsyad; Muhammad Rifky Fahreza; Mutiara Dwi Astuti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Before undertaking the Hajj trip, it is very important to ensure the health condition of the pilgrims. The results of various stages of health tests are used to determine the current health condition of the congregation. This research conducted a literature review from various trusted sources using qualitative research methodology. The findings of this study indicate that the results of various stages of health examinations are used to assess the health condition of pilgrims during the Hajj pilgrimage. A person's health status to perform the Hajj pilgrimage is determined by four factors, namely fulfilling the Hajj requirements without assistance, fulfilling the Hajj requirements without assistance, not meeting the temporary Hajj health requirements, and not meeting the health requirements. Hajj health istithaah. The Ministry of Religion and the Ministry of Health are currently preparing a new plan regarding health istitha'ah requirements for Hajj pilgrims to encourage strategies for fulfilling health istitha'ah. In an effort to reduce the number of pilgrims who get sick and die while in Saudi Arabia, this new program will tighten health requirements for Hajj pilgrims. Therefore, the assessment of the health of Hajj pilgrims relies on the findings of various health examinations and is an important prerequisite before starting the journey.